Effect of pomegranate (Punica granatum) anthelmintic treatment on milk production in dairy sheep naturally infected with gastrointestinal nematodes - Castagna, Fabio; Bava, Roberto; Palma, Ernesto; Morittu, Valeria; Spina, Antonella; Ceniti, Carlotta; Lupia, Carmine; Cringoli, Giuseppe; Rinaldi, Laura; Bosco, Antonio; Ruga, Stefano; Britti, Domenico; et al. (Frontiers in Veterinary Science, 2024)
Anthelmintic drug resistance has proliferated across Europe in sheep gastrointestinal nematodes (GINs). Sheep welfare and health are adversely impacted by these phenomena, which also have an impact on productivity. Finding alternatives for controlling GINs in sheep is thus of utmost importance. In this study, the anthelmintic effectiveness (AE) of a Calabrian ethnoveterinary aqueous macerate based on Punica granatum (whole fruits) was assessed in Comisana pregnant sheep. Furthermore, an examination, both qualitative and quantitative, was conducted on milk. Forty-five sheep were selected for the investigation. The sheep were divided by age, weight, physiological state (pluripara at 20 days before parturition) and eggs per gram of faeces (EPG) into three homogeneous groups of fifteen animals each: PG received a single oral dosage of P. granatum macerate at a rate of 50 milliliters per sheep; AG, treated with albendazole, administered orally at 3.75 mg/kg/bw; CG received no treatment. Timelines were as follows: D0, treatments, group assignment, faecal sampling, and AE assessment; D7, D14, D21, fecal sampling and AE evaluation. The FLOTAC technique was used to evaluate the individual GIN fecal egg count (FEC) using a sodium chloride flotation solution (specific gravity=1.20) and 100×(1-[T2/C2]) as the formula for evaluating FEC reduction. Following the lambs' weaning, milk was collected on the following days (DL) in order to quantify production: DL35, DL42, DL49, DL56, DL63, DL70, DL77, and DL84. The amount of milk produced by every This is a provisional file, not Formattato: Giustificato Formattato: SpazioPrima: 0 pt, Dopo: 0 pt ha formattato: Tipo di carattere: Corsivo the final typeset article individual was measured and reported in milliliters (ml) for quantitative evaluations. Using milko Scan TM fT+foss electric, Denmark, the quality of the milk (casein, lactose, protein concentration, and fat, expressed as a percentage) was assessed. The macerate demonstrated a considerable AE (51.8%). Moreover, its use has resulted in higher milk production rates quantitatively (15.5%) and qualitatively (5.12% protein, 4.12% casein, 4.21% lactose, and 8.18% fat). The study showed that Green Veterinary Pharmacology could be the easiest future approach to counteract anthelmintic resistance in sheep husbandry.